The Dawn of the 3d Spray - Xyntarianos Tsiropinas, Paris (2020)
The diversity of techniques, methods and tools in creating Graffiti and Street Art allows artists to constantly evolve and discover new ways to express their ideas and implement their work. At the same time, a large number of researchers study and observe artists and their work, in an attempt to experiment with the emergence and spread of the phenomenon of urban art in combination with other scientific environments, such as engineering, robotics, programming and more. In this article, after the introduction to the power and importance of spray paint as a tool and symbol for the evolution of urban art, a first glimpse on the street artist - designer follows. This new type of creator can intervene radically in shaping the urban landscape by properly utilizing the designers’ toolbox to help innovative ideas come to fruition. One of these ideas is to use polyurethane foam as a "three-dimensional spray". Using it, the artist can create embossed or three-dimensional works on a large scale, taking existing practices one step further. A case study illustrated by a variety of images is presented before the conclusion of this paper, describing the creation of a lion's head directly on the wall using polyurethane foam spray and then painting it with graffiti spray paint.